(untitled) (Orfeu, 2020)
In this article we discuss how Paraguayan popular music, especially those of the purahei jahe’o polka type, can be used as fundamental material. We selected the song Propiedad Privada as material for analysis and we deduced two aspects from it: (i) the situation of women in Paraguayan culture and (ii) land dispute. Both aspects appear in the lyrics of the song from a certain ambiguity of meaning. It cannot be said with certainty whether the lyrics refer to one or the other subject. The power of the song, from our perspective, lies precisely in that capillarity that allows the two themes to be connected. And from these two aspects that seem disparate, we are discovering an important part of Paraguayan history and the characteristic elements of its culture. Unfortunately, we also see the reiteration of social violence that keeps the oppressed in a condition of servility and poverty.